THE USE OF PROJECT BASED LEARNING TO IMPROVE THE STUDENTS’ SPEAKING PERFORMANCE - Agustiawati, Hartini; Elfarissyah, Andriamella; Lestari, Winda (English Community Journal, 2024)
English as a foreign language has important role in our life especially for students who want to reach their dreams to work or study in abroad. They must have a skill to speak and communicate in English. There are many problems for teachers to teach English in the classroom, Such as low motivation, lazy to practice and a little time to teach. These problems are familiar to students who learn English as a Foreign language. Therefore, teachers need strategies to motivate and encourage students to learn, read and practice English. In order to help students to speak effectively, a strategy can be used. Project based learning is a suitable strategy to develop students to speak and it motivates students to practice and show their performance in speaking English.